Afectación al contratista por procesos de administración de los proyectos durante la ejecución de obras hidráulicas. - Caiza Haro, Paulo Andrés (2024)
The main objective of this research study was to focus on the inefficient administrative processes in the management of water works can affect the scope, budget and timeframe of a project, thus directly affecting the contractor who has a contractual commitment with a public institution. It will analyze the administrative processes during the life cycle of a project and the interaction of the different stakeholders involved in them, thus identifying critical points. The research seeks to identify, analyze and quantify the impact on contractors due to the administrative processes they must follow throughout the life cycle of a hydraulic work. This study focuses on identifying how administrative processes can have an economic and emotional impact on contractors of hydraulic works projects in order to propose improvements in administrative processes during the management of hydraulic works. The methodology focused on conducting a baseline analysis based on hydraulic projects executed in the period 2019-2023 in the province of Chimborazo that have Provisional Reception in order to determine the deadlines in the stages in which the life cycle of a hydraulic work has been divided. In addition, surveys were carried out among contractors in relation to the administrative processes during the management of hydraulic works and to establish the impact on them.